2019
DOI: 10.1002/jcad.12286
|View full text |Cite
|
Sign up to set email alerts
|

Hope as a Mediator of Bullying Involvement and Emotional Difficulties in Children

Abstract: This study investigated hope as a mediator between children's bullying involvement and emotional difficulties in a sample of 1,060 school-age children (Grades 3-6). Results from structural equation modeling suggested that victimization leads to emotional difficulties both directly and indirectly through hope. Perpetration was indirectly associated with emotional difficulties. Findings highlight the role of children's cognitive-motivational process for emotional well-being in response to bullying involvement. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
(103 reference statements)
0
4
0
2
Order By: Relevance
“…Prati et al (2018) also found that peer victimization predicted lower levels of life satisfaction in their study of 1076 adolescents. Although these findings support the negative influence of peer victimization on life satisfaction among adolescents, investigating children's bullying experience has received far less attention (Carney et al, 2019). Given the longterm effects of the early exposure to peer victimization (Rudolph et al, 2011), it is vital to better understand children's victimization experiences in order to better mitigate harmful effects of victimization on students' wellbeing.…”
Section: Victimization and Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prati et al (2018) also found that peer victimization predicted lower levels of life satisfaction in their study of 1076 adolescents. Although these findings support the negative influence of peer victimization on life satisfaction among adolescents, investigating children's bullying experience has received far less attention (Carney et al, 2019). Given the longterm effects of the early exposure to peer victimization (Rudolph et al, 2011), it is vital to better understand children's victimization experiences in order to better mitigate harmful effects of victimization on students' wellbeing.…”
Section: Victimization and Life Satisfactionmentioning
confidence: 99%
“…Ttofi et al (2011) conducted a systematic review of longitudinal studies and found that peer victimization was a major risk factor that uniquely predicted children's depression later in life, even after controlling for other major childhood risk factors. These findings underscore the need for school counselors' timely interventions to mitigate the longterm impact of peer victimization on children's mental health concerns (Carney et al, 2019). Previous studies primarily focused on the negative outcomes of victimization, and limited research investigated the link between victimization and positive well-being, such as life satisfaction (Vera et al, 2015).…”
Section: Victimization and Life Satisfactionmentioning
confidence: 99%
“…Counselors could integrate those techniques in their classroom guidance lessons, small groups, and individual sessions to increase children's hope level about their career future. Monitoring and supporting children's cognitive‐motivational process and helping them identify obstacles will help them envision alternative strategies to achieve their goals (Carney et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…También, se ha demostrado que la esperanza es un factor protector clave en la juventud, habiendo evidencia que los adolescentes con niveles más altos de esperanza tienen menor riesgo de experimentar problemas internalizantes 15,16 . Además, la esperanza se ha asocia-do a mejor rendimiento académico y menores problemas conductuales 17 . En población infantil, la esperanza se ha vinculado a menos dificultades y victimización en contextos de violencia escolar 17 y como moderadora de la discriminación percibida 18 .…”
Section: Introductionunclassified
“…Además, la esperanza se ha asocia-do a mejor rendimiento académico y menores problemas conductuales 17 . En población infantil, la esperanza se ha vinculado a menos dificultades y victimización en contextos de violencia escolar 17 y como moderadora de la discriminación percibida 18 . Por tanto, los estudios de esperanza en NNA la caracterizan como una fortaleza psicológica que ayuda a los NNA a lidiar con eventos adversos de la vida 3,11,16,19,20 .…”
Section: Introductionunclassified